Property and power in social theory : a study in intellectual rivalry - Pels, Dick, 1948- (Routledge studies in social and political thought, 1998)
Property and power perform a key role in social and political theories of class inequality and social stratification, however, theorists have yet clearly to define these concepts, their mutual boundaries and scopes of application. This book answers the property/power puzzle by undertaking a broad historical inquiry into its intellectual origins and present-day effects through a series of case studies, including:Marxism vs. anarchism* the fascist assertion of the primacy of the political* social science as power theory* the managerial revolution* the knowledge society and th.